The challenge of immunogenicity in the quest for induced pluripotency. - Fairchild, P (2010)
Few advances have been so widely acclaimed in biology as the seminal demonstration that adult somatic cells can be induced to acquire the phenotype and differentiation potential of embryonic stem cells. The capacity to produce patient-specific stem cells that are truly pluripotent has raised prospects for the treatment of many degenerative diseases through replacement of the affected cell types. In the race to the clinic, however, questions surrounding the potential immunogenicity of such cells have been largely overlooked. Here, I explore the extent of the challenges ahead and suggest that the induction of tolerance to such cells will be crucial to the future success of induced pluripotency.